Uso de los cuentos infantiles para el desarrollo de la atención en un aula de cuatro años de una institución educativa privada de Miraflores - Falcon Pacherres, Tamara Crys (2025)
The use of children’s stories in early childhood allows for the strengthening of various social and cognitive skills, including attention. The present research seeks to answer the following question: How children’s stories are used to develop attention in a fouryear classroom of a private educational institution in Miraflores. The general objective is to analyse the use of children’s stories to develop attention in a four-year classroom of a private educational institution in Miraflores, from which two specific objectives emerged: to describe the educational perceptions about the development of attention in a four-year classroom of a private educational institution in Miraflores and, on the other hand, describe educational strategies to develop attention through the use of children’s stories in a four-year classroom at a private educational institution in Miraflores. The present study is descriptive because it describes the use that the teacher gives to children’s stories for the development of care by applying the instruments and techniques of data collection: the semi-structured interview and observation guide. This study concludes that children’s stories are used as a tool for the development of attention to children through the use of gestural and corporal expression, support materials and verbal interaction proposed by the teacher.